SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN LOKASI PENDIRIAN HOTEL BARU BERBASIS ANALYTICAL HIERARCHY PROCESS (AHP) DI KABUPATEN KULON PROGO - Yuli Praptomo PHS (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2018)
Decision Support Systems or Decision Support Systems (DSS) are defined as interactive computer-based systems, which help decision makers to use data and models to solve unstructured problems. Decision Support Systems are interactive computer systems that can provide alternative solutions for decision makers, so decisions can be made more quickly and accurately. In an effort to speed up the decision-making process and avoid the subjectivity of the resulting decisions a decision support system is needed that aims to assist job management as decision makers in deciding the right location to establish new hotels through the selection process using the Analytical Hierarchy Process (AHP) model. This system is expected to assist management in comparing value criteria, applying pairwise comparison matrices to get the weight of each criterion both local and global criteria. The AHP method is chosen because this method can carry out multi-objective measurements and several criteria, according to the requirements in the decision for the establishment of new hotels that rely on criteria.